A study on sustainable growth rate for firm survival1. (2nd July 2019) - Mamilla, Rajesh
Abstract: Understanding where a company is in its life cycle is important. The sustainable growth rate (SGR) is an indicator of what stage a company is in, in its life cycle. The position often determines corporate finance objectives such as what sources of financing to use, dividend pay‐out policies, or overall competitive strategy. The purpose of this study is to analyze the actual growth rate as well as SGR and investigate the overall effect of selected independent variables on SGR.